Cultivating Collaboration in Civics Education at SDN 1 Purbosuman - Fernanda Arma Yudithira; Sutama Sutama (FKIP - Universitas Riau, 2026)
Collaboration is an important component of character education in elementary schools, yet teacher-centered instruction may limit students’ opportunities to develop collaborative skills through authentic learning experiences. This study aimed to describe the cultivation of collaboration through active cooperation and concern for the common good in elementary school Civics Education (PPKn). A qualitative case study was conducted at SDN 1 Purbosuman Ponorogo involving the school principal, one Grade V Civics Education teacher, and Grade V students. Data were collected through classroom observations, semi-structured interviews, and photographic documentation. The credibility of the findings was established through source and method triangulation by comparing and integrating evidence across participants and data collection methods before drawing conclusions using the interactive model of Miles and Huberman. The findings showed that active cooperation was cultivated through group discussions, shared responsibilities, peer assistance, and project-based activities facilitated by teachers. Concern for the common good was fostered through contextual learning, peer assistance, social activities, and a positive school culture emphasizing empathy and collective responsibility. These findings provide practical guidance for Civics Education teachers to design authentic collaborative learning experiences that simultaneously strengthen students’ cooperation, empathy, social responsibility, and civic character in elementary schools.